Feature extraction in batik image geometric motif using canny edge detection - Muhammad Fikri Hidayattullah; M. Nishom; Slamet Wiyono; Yustia Hapsari (Jurnal Informatika, 2020)
One of Indonesia's priceless cultural heritages is batik. Even UNESCO was admitting that batik is an intellectual, cultural right of the Indonesian (October 2). Unfortunately, many Indonesian do not have sufficient knowledge about the various types of the existence of batik's motifs. In fact, in each of these motifs, many treasures must be maintained. Therefore, it is necessary to develop a model that can recognize batik motifs automatically. The model can be built using various kinds of pattern recognition algorithms. One of the most important stages in the introduction of batik motifs is the feature extraction. Feature extraction is needed to determine the parameters that able to define character a batik's motif. One feature extraction model that can be done is by using edge detection. This research focuses on feature extraction using Canny edge detection. The result of edge detection is forming the pattern of a batik motif. The pattern contains pixel values 0 and 1. These values can later be used as input at the classification stage.